Competencia entre malezas y cultivos. Análisis de la interferencia de las malezas sobre el cultivo de lino oleaginoso - Verona, Carlos Alberto; Fernández, Osvaldo Néstor; Löffler, Carlos Marcelo (Ecosur, 2025)
This paper deala with the competition between crops and weeds from an ecologkal point of view. As a general introduction to the competition between plants the theory, in biological systems, was critically reviewed. The conceptual evolution of the “principie of competitive exclusión", and the analogies and diíferences between animáis an plants, in relation with competition processes were evaluated. Factors and mechanisms of competition in plants were considered in order to show the advantages, limitations and consecuences that result from the use of different experimental designa. One aspect that received our special attention was the conceptual model that we ougth to assume in order to represent a weedy-crop when we want to study it as a competition system. Essays were conceived and carried-out as a way to discrimínate the interaction between: i) the interference processes and the sowing date; and, ii) the effect of the interference processes at one developmental stage of the crop, and the one produced previously or that could be produced subsequently at any other deveipmental stage. In this way the behavior of the oil-flax was studied by means of field experiments including two sowing dates and different regimes of weed remo val, conducted in two different years, in order to explain the interference process between the crop plants and their companion flora.